2021
DOI: 10.1371/journal.pone.0248196
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of fibroblast activation protein alpha attenuates left ventricular dilation after myocardial infarction

Abstract: Introduction Regulating excessive activation of fibroblasts may be a promising target to optimize extracellular matrix deposition and myocardial stiffness. Fibroblast activation protein alpha (FAP) is upregulated in activated fibroblasts after myocardial infarction (MI), and alters fibroblast migration in vitro. We hypothesized that FAP depletion may have a protective effect on left ventricular (LV) remodeling after MI. Materials and methods We used the model of chronic MI in homozygous FAP deficient mice (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…FAP has dipeptidyl peptidase and endopeptidase activities, its substrates are largely unknown ( 22 ). Preclinical models targeting FAP show that FAP knockout is not associated with disease ( 23 , 24 ) Circulating FAP cleaves alpha2-antiplasmin, which thereby becomes a potent inhibitor of plasmin, leading to a reduction in fibrinolysis ( 22 ). This fact supports our findings by higher NIHSS scores in patients with lower FAP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…FAP has dipeptidyl peptidase and endopeptidase activities, its substrates are largely unknown ( 22 ). Preclinical models targeting FAP show that FAP knockout is not associated with disease ( 23 , 24 ) Circulating FAP cleaves alpha2-antiplasmin, which thereby becomes a potent inhibitor of plasmin, leading to a reduction in fibrinolysis ( 22 ). This fact supports our findings by higher NIHSS scores in patients with lower FAP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some results suggest The ROC curve for predicting calcified plaques by myocardial FAPI uptake (SUV mean ) in LAD, LCX, and RCA territory showed areas under the curve (AUCs) were 0.786 (95%CI: 0.581-0.99), 0.759 (95%CI: 0.521-0.998), and 0.769 (95%CI: 0.559-0.978), respectively. that FAP is not crucial for cell proliferation, adherence and migration within the myocardium after MI (8). The lack of noninvasive tools that can monitor fibroblast activation in humans, however, has limited the success of translating these results to human patients.…”
Section: Discussionmentioning
confidence: 99%
“…After the coronary injury, Varasteh et al showed that 68 Ga-FAPI uptake peaked at day 6 post-MI, most of which occurred in the border-ischemic area ( 5 ). In contrast, some results suggest that FAP is not crucial for cell proliferation, adherence and migration within the myocardium after MI ( 8 ). The lack of non-invasive tools that can monitor fibroblast activation in humans, however, has limited the success of translating these results to human patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations